Income from Processing Alcoholic Beverages (Sopi) on the Socio-Economic Conditions of Families in Hutumuli Hamlet, Piru Village, West Seram District, West Seram Regency - Somahu, Natalis; Pinoa, Wiclif Sepnath; Sihasale, Daniel Antoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Economic development in Indonesia must face the reality that poverty is still widespread, especially in rural areas, which burdens residents. Rural development is a strategy stimulated to improve the economic and social life of particular groups of people, namely people in rural areas, one of which is Hutumuli Hamlet. Hamlet Hatumuli is relatively backward socio-economically (especially regarding access to education and the economy) and culturally compared to other community groups. The people of Hatumuli Hamlet are marked by several characteristics such as poverty, socio-cultural backwardness, and low human resources (HR). The people of Hatumuli Hamlet, West Seram Regency, are not a few who are still not economically prosperous, which can be said to be lacking. In everyday life, the economy needs to fulfil these needs. Therefore, the economy is a critical need in human life. The people of Hatuumuli Hamlet have a meagre economy. However, over time, the economic situation in Hatumuli Hamlet has been supported by the processing of sopi, so it has stayed the same, unlike before. Income from some processing is one of the supporting factors for the advancement of the economy in Hatumuli Hamlet, so now what is being managed can be said to be one of the jobs that can trigger and encourage the community's economy and can result in the results obtained not only meeting basic needs but also providing improvement and progress. The research used is qualitative research, which presents data descriptively to describe the phenomena that occur at the research location and then explains using frequency tables and pictures.